(untitled) (Modern education and development, 2025)
Cervical diseases have important clinical significance for women’s reproductive health. This topic will cover the main types of cervical diseases, their symptoms, methods of diagnosis and treatment. In particular, pathologies such as cervical cancer, erosions, polyps, stenosis, inflammatory diseases and HPV infection are analyzed. Cervical cancer is associated with human papillomavirus (HPV), and the importance of Pap and HPV testing is emphasized in early diagnosis. The clinical signs of erosions and polyps, and the consequences of inflammatory processes are also highlighted. Cervical pathologies not only increase the risk of cancer, but can also provoke problems such as infertility and miscarriage.